Size Structure and Sex Ratio of Black Tip Reef Shark (Carcharhinus melanopterus) Landed in the TPI Paotere of Makassar City and TPI Beba of Takalar Regency, Province South Sulawesi - Amir, Faisal; Mallawa, Achmar; Tresnati, Joeharnani (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Carcharhinus melanopterus in the southern waters of the Makassar Strait is caught with bottom longlines and bottom gill nets as bycatch, caught throughout the year without any management arrangements. The research objective was to obtain information about the size structure and sex ratio of C. melanopterus in the southern waters of the Makassar Strait. The method used is a survey method. Sample measurements were carried out at TPI Paotere Makassar City and TPI Beba Takalar Regency, South Sulawesi Province from July to September 2020. Measurement of total body length (TL:cm) and determining the sex ratio were carried out directly in the field. The results of the study on 144 sample fish showed that the total length range for C. melanopterus landed at the Paotere TPI was the same as those landed at the Beba TPI at sizes between 58 - 135 cm TL with an average length of 91.18 ± 3.32 cm TL and sizes between 51 - 139 cm TL with an average length of 91.1±2.21 cm TL for both male and female sex, respectively.The comparison of C. melanopterus landed in the two fish landing sites was in a balanced state but the male sex was smaller than the female sex.The sex ratio of male and female C. melanopterus is balanced. Most (69.44%) female C. melanopterus caught were relatively young.